Comparison of spikers' distance covered in elite female volleyball - Hank, M.; Zahalka, F.; Maly, T. (Sport Science - International Scientific Journal of Kinesiology, 2015)
The primary objective of this study was to evaluate, quantify and compare the total distance of movement of elite female volleyball players in horizontal plane during matches. The research group was composed of elite women players of volleyball at Champions League level (n = 8; age = 26 ± 5 years; height = 184.1 ± 5.3 cm; weight = 70.3 ± 4.2 kg). In order to analyse horizontal distance of movement in the match 3D kinematic analysis was used. Objectification of position and movement of individual players was processed using TemaBio 3.2 software. Head position of each player was associated to determine the player`s position on the court. The measurement consisted of four sets from two different matches (total amount of 207 rallies). The average distance of movement of the spiker in one rally was 8.5 m. The minimum distance was 1.06 m. The maximum distance of that player in one rally was 34.12 meters. The average total distance of the spiker`s movement during one set was 398 m. The results showed an ability to evaluate movement distance of female volleyball players and homogeneous volume of load of spikers in a volleyball match.